Remote at-home wearable-based gait assessments in Progressive Supranuclear Palsy compared to Parkinson’s Disease - Mansi Sharma; Ram kinker Mishra; Anna J. Hall; Jose Casado; Rylee Cole; Adonay S. Nunes; Gregory Barchard; Ashkan Vaziri; Alexander Pantelyat; Anne-Marie Wills (BMC Neurology, 2023)
Abstract Background Wearable sensors can differentiate Progressive Supranuclear Palsy (PSP) from Parkinson’s Disease (PD) in laboratory settings but have not been tested in remote settings. Objectives To compare gait and balance in PSP and PD remotely using wearable-based assessments. Methods Participants with probable PSP or probable/clinically established PD with reliable caregivers, still able to ambulate 10 feet unassisted, were recruited, enrolled, and consented remotely and instructed by video conference to operate a study-specific tablet solution (BioDigit Home ™) and to wear three inertial sensors (LEGSys™, BioSensics LLC, Newton, MA USA) while performing the Timed Up and Go, 5 × sit-to-stand, and 2-min walk tests. PSPRS and MDS-UPDRS scores were collected virtually or during routine clinical visits. Results Between November, 2021- November, 2022, 27 participants were screened of whom 3 were excluded because of technological difficulties. Eleven PSP and 12 PD participants enrolled, of whom 10 from each group had complete analyzable data. Demographics were well-matched (PSP mean age = 67.6 ± 1.3 years, 40% female; PD mean age = 70.3 ± 1.8 years, 40% female) while disease duration was significantly shorter in PSP (PSP 14 ± 3.5 months vs PD 87.9 ± 16.9 months). Gait parameters showed significant group differences with effect sizes ranging from d = 1.0 to 2.27. Gait speed was significantly slower in PSP: 0.45 ± 0.06 m/s vs. 0.79 ± 0.06 m/s in PD (d = 1.78, p < 0.001). Conclusion Our study demonstrates the feasibility of measuring gait in PSP and PD remotely using wearable sensors. The study provides insight into digital biomarkers for both neurodegenerative diseases. Trial registration ClinicalTrials.gov Identifier: NCT04753320, first posted Febuary 15, 2021.